Judicial Trend in Protecting Human Rights of Persons in Police Custody - Kumar, N Krishna (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
A person is not liable to be arrested merely on the suspicion of complicity in an offence. The date and time of arrest shall be recorded in the memo which must also be countersigned by the arrestee. The right to counsel begins when a person is being interrogated and continues through pre-trial stages to trial and into appeal since it is an essential ingredient of the reasonable, fair, and just procedure. It would be prudent for the police officer to allow a lawyer where the accused wants to have one at the time of interrogation if he wants to escape the censure that the interrogation is carried on in secrecy by physical and psychic torture. However, these formalities are not followed in all cases and all countries. The higher police officials, even though they may privately be critical of the actions of the lower officials, are tending to protect their fellowmen or the government from civil liability.Keywords: Arbitrary Arrest; Custodial Death; Judicial Review; Torture, Victim Tren Peradilan dalam Melindungi Hak Asasi Manusia dalam Penahanan Polisi AbstrakSeseorang tidak bertanggung jawab untuk ditangkap hanya karena dicurigai terlibat dalam suatu pelanggaran. Tanggal dan waktu penangkapan harus dicatat dalam memo yang juga harus ditandatangani oleh orang yang ditangkap. Hak atas nasihat dimulai ketika seseorang diinterogasi dan berlanjut melalui tahap pra-peradilan hingga persidangan dan naik banding karena ini merupakan unsur penting dari prosedur yang masuk akal, adil, dan adil. Akan lebih bijaksana bagi petugas polisi untuk mengizinkan pengacara di mana terdakwa ingin memilikinya pada saat interogasi jika dia ingin menghindari kecaman bahwa interogasi dilakukan secara rahasia dengan penyiksaan fisik dan psikis. Namun, formalitas ini tidak diikuti di semua kasus dan semua negara. Pejabat polisi yang lebih tinggi, meskipun mereka secara pribadi mengkritik tindakan pejabat yang lebih rendah, cenderung melindungi sesamanya atau pemerintah dari pertanggungjawaban perdata.Kata Kunci: Penangkapan Sewenang-wenang; Penahanan Mati; Peninjauan Kembali; Penyiksaan; Korban Судебные Тенденции В Защите Прав Человека При Содержании Под Стражей В Полиции Аннотация Никто не может быть арестован только по подозрению в причастности к преступлению. Дата и время ареста должны быть записаны в памятной записке, которая также должна быть подписана арестованным. Право на консультацию начинается с допроса человека и продолжается на досудебной стадии до суда и апелляции, поскольку это важный элемент разумной и справедливой процедуры. Было бы разумно, если бы полицейский допустил адвоката, которого обвиняемый хочет иметь во время допроса, если он хочет избежать критики в связи с тем, что допрос проводится тайно с применением физических и психологических пыток. Однако эта формальность соблюдается не во всех случаях и не во всех странах. Высокопоставленные полицейские, даже если они лично критиковали действия низших должностных лиц, как правило, защищали себя или правительство от гражданской ответственности.Ключевые Слова: Необоснованный Арест; Смерть В Условиях Содержания Под Стражей; Судебный Пересмотр; Пытки, Жертва